2013
DOI: 10.1016/j.celrep.2013.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking Multivesicular Bodies Enables Long-Term and Exosome-Mediated Long-Distance Action of Anthrax Toxin

Abstract: SUMMARY Anthrax Lethal Toxin is a classical AB-toxin comprised of two components, Protective Antigen (PA) and Lethal Factor (LF). Here we show that following assembly and endocytosis, PA forms a channel that translocates LF, not only into the cytosol, but also into the lumen of endosomal intraluminal vesicles (ILVs). These ILVs can fuse and release LF into the cytosol, where LF can proteolyze and disable host targets. We find that LF can persist in ILVs for days, fully sheltered from proteolytic degradation, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(146 citation statements)
references
References 36 publications
6
136
1
3
Order By: Relevance
“…Although the release of endocytosed toxins back into the extracellular medium has been previously described for the plant toxin ricin (88)(89)(90) and for anthrax toxin (91), neither of those toxins has been reported to follow the endocytic recycling route (91,92). The release of endocytosed ricin seems to occur through a mechanism involving exocytosis of multivesicular bodies (89), allowing intoxication of bystander cell populations (90).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the release of endocytosed toxins back into the extracellular medium has been previously described for the plant toxin ricin (88)(89)(90) and for anthrax toxin (91), neither of those toxins has been reported to follow the endocytic recycling route (91,92). The release of endocytosed ricin seems to occur through a mechanism involving exocytosis of multivesicular bodies (89), allowing intoxication of bystander cell populations (90).…”
Section: Discussionmentioning
confidence: 99%
“…The release of endocytosed ricin seems to occur through a mechanism involving exocytosis of multivesicular bodies (89), allowing intoxication of bystander cell populations (90). In the case of anthrax, it has been demonstrated that the toxin is delivered into the extracellular medium in exosomes, contributing to prolonged toxicity and possibly to transmission of the toxin to distant cells (91). During this work, several attempts were made to detect activity of recycled AIP56.…”
Section: Discussionmentioning
confidence: 99%
“…anthracis virulence factor, is translocated into the lumen of endosomal intraluminal vesicles (ILVs), persists in them for days and can be transmitted to neighboring cells [15]. Trichosanthin (TCS), a plant toxin, is incorporated into intraluminal vesicles of the MVB and is then secreted in association with exosomes upon fusion of the MVB with the plasma membrane [16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, LF can be transported not only into the cytosol but also into the lumen of endosomal intraluminal vesicles. The vesicles fully protect LF from proteolytic degradation and significantly later fuse and release LF into the cytosol [114]. These findings may indicate that the focus of anthrax antitoxin research should be shifted toward LF.…”
Section: Polyvalent Cationic Pore Blockersmentioning
confidence: 98%